The effect of play media health education on fluid restriction adherence in chronic renal failure patients in the hemodialysis room of RSU Haji Medan in 2023 - Ainun, Kamaliah; Pase, Muslimah (Sean Institute, 2024)
Chronic kidney failure is a disease in which the body fails to maintain metabolism and fluid and electrolyte balance. Based on data from the Indonesia Renal Registry (IRR), as many as 98% of patients with Chronic Kidney Disease (CKD) undergo Hemodialysis therapy and 2% undergo peritoneal dialysis (PD) therapy. This study aims to analyze the effect of health education with Play Media on fluid restriction compliance in chronic kidney failure patients in the Hemodialysis Room of RSU Haji Medan in 2023. This type of research is quantitative research using Experimental Research with quasi-experiments, Design One group pretest-posttest only design. The population in the study of all CKD patients with a total of 42 people, the sampling technique is non-probality sampling in the form of Purposive sampling, which meets the inclusion criteria of 21 people. Data collection method using questionnaires. The statistical test used is the Wilcoxon Sign Rank Test with a value of α 0.05. The results of this study are known that before health education was given, the majority of whom were non-compliant as many as 19 people (90.%) and after being obedient to 17 people (81.0%), the results of the Wilccoxon Sign Rank Test Analysis obtained a p-value of 0.000 (< 0.05) meaning that Ho was rejected Ha was accepted, meaning that there is an influence of health education on fluid restriction compliance in chronic kidney failure patients in the Hemodialysis Room of RSU Haji Medan in 2023, with a value of Z (3.844). The conclusion of the study shows that there is an influence of rotary media health education on fluid restriction compliance in chronic kidney failure patients in the Hemodialysis Room of RSU Haji Medan In 2023, it is expected that Haemodialysis room officers will provide counseling to patients in fluid restriction.